Hypertension: smoking or quit. Clinical difficulties - N. V. Korneeva; E. S. Gavrilov (Кардиоваскулярная терапия и профилактика)
The review describes the combination of hypertension (HTN) and smoking in the same person. The prevalence of this combination in the Russian population is high due to the widespread prevalence of both HTN and smoking. There are following unidirectional negative impact of both factors on vascular system: endothelium, microcirculation, large vessel stiffness, contributes to higher blood pressure among such patients and leads to early target organ damage, increased cardiovascular and death risk. Smoking cessation is the main effective measure of primary and secondary prevention among smoking patients with HTN. The review provides links to well-known articles and the results of studies showing the benefits of smoking cessation. However, it is not easy for smoking patients with hypertension to quit smoking: on the one hand, nicotine addiction, similar to drugs, through central nervous system exposure, makes the habit stable, while on the other hand, the low motivation of such patients due to young age and the absence of current smoking consequences, which complicates working with such patients. Knowledge of algorithms for working with smoking patients and methods of non-drug support can help practitioners supporting such patients at the stage of smoking cessation.